Effective Estimation Method of Basic Parameters of MOS Structures - E., Montrimas; A., Pazera; S., Sakalauskas (Elektronika ir Elektrotechnika, 2000)
A new operative and simple estimation method of parameters of MOS structures is proposed. This method may be succesfully applied in industry as well as for scientific research purposes. For this is enough, by using linearly increasing voltage, to measure C-V and charge current density dependences of MOS sructure, and, after not complicated mathematical treatment of results, to obtain main parameters: voltage of flat bands, equivalent charge in dielectric layer, density of dopants, thickness of depletion region, permittivities of semiconductor and dielectric layer. Parameters of the investigated MOS (KDB-10) structures determined using the above-mentioned method are the following: flat-band voltage Ufb = (6,9± 0,1) V, equivalent charge of the SiO2 layer QSiO2 = (7,45± 0,15)× 10-8 C/cm2, density of impurities introduced into the semiconductor Na = (1,33± 0,10)× 1015 cm-3, maximum thickness of the depletion layer w(t) = (0,9± 0,1) m m, dielectric constant of the SiO2 layer e 1 = 4,1± 0,15. These values are in accord with corresponding values obtained using other methods of measurement.